User-defined view automation of genomic databases - Robinson, A.; Rahayau, W.; Herd, S.; Dillon, Tharam S. (ACM, 2005)
This paper presents a solution to the problem of creating a subset database from the public genome databases, also known as a database view. While the techniques to generate views are well established already in the database system there are still some problems found where applying this technique in the genome database environment. The main problems that exist in the current methods of view creation are missing relevant results, returning irrelevant results and view creation processes are generally very time consuming for the user. The solution presented within provides an automated approach aimed at reducing the time needed to create a view, which is usually done by hand. The solution improves the searching method needed for view creation by the addition of two extra phases; the first, expanding the keyword search so that it captures all relevant results and second, a filtering phase to remove all the extra irrelevant results. The whole process is done in the background so that the user isn’t required to spend much time fixing the results of inadequate search tools.